Distribution Patterns of Maternal and Child Health in West Sulawesi Province, Indonesia: A Descriptive Analysis from 2017 to 2020 - Ramadhan Tosepu (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Maternal and child health are key indicators for measuring the health status of a population and assessing the success of health sector development. West Sulawesi Province, as one of the provinces in Eastern Indonesia, continues to face significant challenges in reducing maternal and infant mortality rates. Various factors such as geographical accessibility, the availability of healthcare personnel, and social determinants influence the distribution of maternal and neonatal mortality in this region. Objectives: This study aims to describe the distribution of maternal and infant mortality in West Sulawesi Province during the period 2017–2020 based on secondary data obtained from the West Sulawesi Provincial Health Profile. Methods: This study employs a descriptive quantitative method, analyzing secondary data sourced from the Health Profile of West Sulawesi Province. The data analyzed include the annual number of maternal and infant deaths. The analysis was carried out by organizing the data into tables and graphs and narratively interpreting the patterns and trends observed. Results: The findings reveal fluctuations in maternal and infant mortality rates from 2017 to 2020. A decline in infant mortality was observed in certain years, whereas maternal mortality tended to remain stable, albeit at a high rate. Geographic factors, limited health facilities, and socio-cultural influences are estimated to be major contributors to these observed trends. Conclusion: The distribution of maternal and infant mortality in West Sulawesi Province highlights the urgent need for strengthening maternal and neonatal healthcare services, developing an effective referral system, and improving accessibility to healthcare services, particularly in remote areas. Community-based initiatives and evidence-based policies are essential to achieve sustainable health development targets. Keywords: Maternal Mortality, Infant Mortality, Health Distribution, Indonesia